2014
DOI: 10.1016/j.carbpol.2013.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan hydrogel films: Molecular conformation, charge density and protein carriers

Abstract: In this article the molecular conformation of xanthan chains in hydrogel films was investigated by means of circular dichroism, showing substantial differences between xanthan hydrogel prepared in the absence (XNT) and in the presence of citric acid (XCA). The xanthan chains in XNT hydrogels films presented ordered conformation (helixes), while in XCA they were in the disordered conformation (coils), exposing a larger number of carboxylate groups than XNT. The large charge density in XCA hydrogels was evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…For example, Moddaresi et al [15] showed an increase in topical formulation viscoelasticity when lipid nanoparticles were added to hyaluronic acid vehicle. However, it made sense, that neither HPMC or xanthan gum would interact with the nanomaterials used in this work given that the HPMC gel was neutral and the xanthan gum was negatively charged and so they would presumably have limited interactions with the negatively charge nanomaterials [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Moddaresi et al [15] showed an increase in topical formulation viscoelasticity when lipid nanoparticles were added to hyaluronic acid vehicle. However, it made sense, that neither HPMC or xanthan gum would interact with the nanomaterials used in this work given that the HPMC gel was neutral and the xanthan gum was negatively charged and so they would presumably have limited interactions with the negatively charge nanomaterials [37].…”
Section: Discussionmentioning
confidence: 99%
“…Xanthan gum is a branched, high molecular weight exopolysaccaride produced by Xanthomonas campestris 42 . It is composed of D-glycosyl, D-mannosyl, and D-glucuronyl acid in 2:2:1 molar ratio along with variable amounts of O-acetyl and pyruvyl residues 43 . A thermal stimulus causes xanthan gum to undergo a conformational change in aqueous solution from an ordered helix, stabilized by non-covalent bonds, to disordered coil.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Guar gum is neutral, being composed of galactose and mannose (Robinson et al, 1982), while xanthan gum is negatively charged due to glucuronic and pyruvic acid residues amongst the uncharged glucose and mannose along its chain length (Jansson et al, 1975). With an estimated pKa 4.5 (Bueno and Petri, 2014), xanthan gum is expected to be ionized at the pH of water used to prepare the thickened fluid (pH water 5.2 at 23°C). Xanthan gum used in this study also contained 1g/100 g of sodium, which is added to help xanthan gum to form a highly ordered and stable network (Morris et al, 1977), and this electrolyte maybe expected to compete with the atenolol for the interactions.…”
Section: Discussionmentioning
confidence: 99%
“…There was preliminary evidence for an interaction between the positive charge on the weakly basic atenolol (pKa 9.3) and the negative charge on the weakly acidic xanthan gum (estimated pKa 4.5; (Bueno and Petri, 2014), both of which would be ionized at the pH of the water (pH 5.2) used with the thickener. At semi-dilute gum concentrations, diffusion of atenolol was slowed when mixed into xanthan gum but not guar gum, and mechanical spectra were measured for xanthan gum but not guar gum indicating stronger polymer entanglement for the former (Chapter 4).…”
Section: Drug and Dosage Formmentioning
confidence: 99%